Acute and subchronic oral toxicity of oil palm puree in Sprague–Dawley rats - Zainal, Zaida; Ong, Augustine; Choo, Yuen May; Chang, Sui Kiat; Abdul Rahim, Afiqah; Khaza'ai, Huzwah (MDPI, 2020)
Palm puree is rich in antioxidants and is produced via blending various proportions of mesocarp fibre and crude palm oil. The aim of this study was to assess the acute and subchronic toxicity of palm puree in male and female Sprague–Dawley rats. For the acute toxicity study, animals administered single palm-puree doses (2000 mg kg−1) by gavage were observed daily for 14 d. For the subchronic toxicity study, the rats were administered 500, 1000, or 2000 mg kg−1 palm puree daily for 28 d. We evaluated body and organ weights; performed haematological, biochemical, and histopathological analyses of blood and organ samples during and after treatment; and calculated the oral no-observed-adverse-effect level (NOAEL). The toxicity studies showed no signs of toxicity or mortality. The haematological, biochemical, and histopathological analyses and body and organ weights indicated no evidence of substantial toxicity at any dose of palm puree. The oral lethal dose and NOAEL for the palm puree were greater than 2000 mg kg−1 d−1 over 28 d. To the best of our knowledge, the present study is the first to confirm the safety of palm puree as a novel functional food. These encouraging results warrant further studies to elucidate its potential for pharmaceutical formulations.